Impact of pre-oxidation on the reactivity and conductivity in H2–H2O atmosphere of a ferritic stainless steel for high temperature water vapour electrolysis. (1st July 2022) - Ardigo-Besnard, M.R.; Popa, I.; Chevalier, S.
Abstract: The as-rolled K41X (AISI 441) ferritic stainless steel presents unusual behaviour when exposed in H2 –H2 O atmosphere at 800 °C, with growth of non-protective iron oxides at its surface. The impact of pre-oxidation in air is investigated in this paper. The pre-oxidation induces the formation of a thin chromia layer at the steel surface. The results obtained after subsequent oxidation for 100 h in H2 –H2 O atmosphere evidence a change in the surface reactivity behaviour of the as-rolled alloy: iron oxides formation is avoided and high temperature behaviour (reactivity and conductivity) is improved. Air pre-oxidation seems a promising solution for large scale use of K41X as-rolled steel in H2 –H2 O atmosphere at high temperature. Highlights: Pre-oxidation impact on high temperature behaviour of an as-rolled steel is studied. Pre-oxidation leads to the formation of a thin chromia layer at the steel surface. After subsequent oxidation in H2 –H2 O atmosphere iron oxides formation is avoided. High temperature reactivity and conductivity of as-rolled steel are improved. Pre-oxidation represents a large-scale alternative to the mirror polishing process.